1984
DOI: 10.1111/j.2042-3306.1984.tb01941.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemostatic mechanisms of the newborn foal: Reduced platelet responsiveness

Abstract: Summary Whole blood platelet counts, coagulation profiles and in vitro platelet function tests were monitored in newborn foals during the first week of life. Platelet counts, mean platelet volumes and thrombin‐induced malondialdehyde production were not different from adult mares. Prothrombin and partial thromboplastin times were slightly, but not significantly, longer for neonatal blood samples than for mare samples. Platelet aggregation responses to serotonin, arachidonic acid or adrenaline did not change du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

1987
1987
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…Intrauterine growth retardation is an important cause of morbidity and mortality in infants and foals, and the consequences of birth asphyxia can be equally devastating in both species (Johnson and Rossdale 1975;Dorand 1977). Platelet function is similar in the two species (Clemmons, Dorsey-Lee, Gorman and Sturtevant 1984). Susceptibility of the newborn to infection is even greater in foals than in infants, probably because of the total failure of IgG to cross the equine placenta.…”
Section: Comparison Between Human and Equine Neonatology Programmesmentioning
confidence: 89%
“…Intrauterine growth retardation is an important cause of morbidity and mortality in infants and foals, and the consequences of birth asphyxia can be equally devastating in both species (Johnson and Rossdale 1975;Dorand 1977). Platelet function is similar in the two species (Clemmons, Dorsey-Lee, Gorman and Sturtevant 1984). Susceptibility of the newborn to infection is even greater in foals than in infants, probably because of the total failure of IgG to cross the equine placenta.…”
Section: Comparison Between Human and Equine Neonatology Programmesmentioning
confidence: 89%
“…Endotoxin interacts rapidly with the platelet membrane, and endotoxin induced platelet aggregation appears to be mediated by a plasma factor, which is most likely an element of the complement system (Walker and Casey 1985). The absence of consistent thrombocytopenia may be the result of an age related reduced platelet response (Clemmons, Dorsey-Lee, Gorman and Sturtevant 1984) or to a decreased complement activity (Hietala and Ardans 1987). The catheterisation protocol implemented can result in coagulopathy, as suggested by the increased APTT and positive FDP in a control foal at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Our results have similarities with Aoki and Ishii (2012) who reported that the platelet count decreases in foals during the first week after birth. Although Clemmons, Dorsey‐Lee, Gorman, and Sturtevant (1984) noted that there was no difference in platelet count between adult horses and foal.…”
Section: Discussionmentioning
confidence: 99%